Multiple cutaneous metastases of oesophageal squamous cell carcinoma that mimic keratoacanthoma. (March 2016) - Aguiar, H.R.; Calderoni, D.R.; Stelini, R.F.; Andreollo, N.A.; Kharmandayan, P.
Abstract: Cutaneous metastases are a rare finding, and therefore frequently neglected. Among the possible clinical patterns of presentation, keratoacanthoma-like lesions are very infrequent and can be misrepresentative of the true diagnosis. We report a case of multiple cutaneous metastases of oesophageal squamous cell carcinoma affecting the scalp and neck that mimic keratoacanthoma. In spite of the typical clinical presentation, pathological findings corroborated the diagnosis of moderately differentiated squamous cell carcinoma. This case raises the possibility of such a clinical presentation being caused by haematogenous dissemination of distant site visceral tumours. Therefore, the differential diagnosis of multiple keratoacanthoma-like lesions should include metastases of distant site visceral malignancies.